ANALISIS PENGARUH HAMBATAN SAMPING TERHADAP KINERJA KAPASITAS LALU LINTAS PADA JALAN IR. H. JUANDA BEKASI TIMUR - Sukadi; Sahat Martua Sihombing; Lydia Darmiyanti (Fakultas Teknik Universitas Krisnadwipayana, 2022)
Road is a land transportation infrastructure that plays an important role in the land transportation sector, withvery rapid economic growth, there is a surge in road traffic users, while the capacity and performance of roadsthat accommodate the flow of vehicles is not comparable to the surge. The growth of small businesses along theroad makes traffic performance decrease, road side constraints have a very large role on road performance andcapacity. Pedestrians, people crossing, entering and exiting vehicles, vehicles slowing down and also vehiclesstop on the side of the road. Jalan Ir. H. Juanda Bekasi has become the research location, because this road sideactivity is relatively high, causing delays in vehicle speed or traffic jams. The number of access roads in and outof housing is also one factor other than those mentioned above. This research was conducted for 7 (seven days),starting on Monday, November 26, 2018 until December 2, 2018. Retrieval of data through direct observation onthe research object, for traffic volume, vehicle speed and side obstacle data are divided per 15 minutes . Dataanalysis was then performed namely traffic volume, speed, density and road capacity using the Indonesian roadcapacity manual (MKJI) 1997. From the results of the study, obtained a value of capacity without side obstaclesof 1520 Smp/hour, and with side obstacles of 1458 smp/hours, then obviously the service capacity of the road hasdecreased, (DS) by 1.39 from the highest daily yield, and calculated (DS) for the next five years by 2.19 Thisshows that the road side barriers on Ir. H. Juanda Bekasi is very high and very influential on the performance oftraffic capacity.